2021
DOI: 10.3390/molecules26216371
|View full text |Cite
|
Sign up to set email alerts
|

Separation of 44Sc from 44Ti in the Context of A Generator System for Radiopharmaceutical Purposes with the Example of [44Sc]Sc-PSMA-617 and [44Sc]Sc-PSMA-I&T Synthesis

Abstract: Today, 44Sc is an attractive radionuclide for molecular imaging with PET. In this work, we evaluated a 44Ti/44Sc radionuclide generator based on TEVA resin as a source of 44Sc. The generator prototype (5 MBq) exhibits high 44Ti retention and stable yield of 44Sc (91 ± 6 %) in 1 mL of eluate (20 bed volumes, eluent—0.1 M oxalic acid/0.2 M HCl) during one year of monitoring (more than 120 elutions). The breakthrough of 44Ti did not exceed 1.5 × 10−5% (average value was 6.5 × 10−6%). Post-processing of the eluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(154 reference statements)
1
11
0
Order By: Relevance
“…Consistent with prior investigation [ 4 , 13 , 14 ], 44 Ti was efficiently loaded on the resin, and we observed that this material can re-distribute on the column following repeated 44 Sc elutions. This resulted in breakthrough of 44 Ti and has the potential to contaminate the radiopharmaceutical and work space for compounding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior investigation [ 4 , 13 , 14 ], 44 Ti was efficiently loaded on the resin, and we observed that this material can re-distribute on the column following repeated 44 Sc elutions. This resulted in breakthrough of 44 Ti and has the potential to contaminate the radiopharmaceutical and work space for compounding.…”
Section: Discussionsupporting
confidence: 91%
“…In order to harness the potential for this isotope for theranostics, greater availability of the isotope and improved understanding of in vivo stability and pharmacodynamics is required [ 11 13 ]. In this work, we sought to produce and better understand how 44 Sc is excreted in vivo, and to what degree this will impact the radiation burden in research and clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…As such, 44 Ti is of interest as the parent nuclide in the long-lived 44 Ti/ 44 Sc generator system. 44 Sc can be chemically separated to create an essentially perpetual source of 44 Sc. For PET imaging, 45 Ti ( t 1/2 = 3.08 h, β + = 85%, and E ⟨β + ⟩ = 0.439 MeV) , offers higher inherent resolution and fewer concomitant γ emissions than any other short-lived radionuclide except 18 F . We and others have demonstrated the chelation and targeting of 45 Ti, revealing a potential path to its application in nuclear medicine .…”
Section: Introductionmentioning
confidence: 95%
“…15–17 Specifically, bifunctional chelators, peptides and biomolecules utilized as disease-specific targeting vectors typically require a pH range of 4–8 to form stable complexes. 18–22…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Specically, bifunctional chelators, peptides and biomolecules utilized as disease-specic targeting vectors typically require a pH range of 4-8 to form stable complexes. [18][19][20][21][22] To enable the concerted separation and labeling with radiometals, we proposed the immobilization of a radiopharmaceutical synthesis precursor comprised of a chelator linked peptide appended to a water-compatible solid-support with a photo-labile amino acid. We drew inspiration from solidphase synthesis approaches of metal-based drugs and the clinical, solid-phase based radiosynthesis 131 I-MIBG, 23,24 and recently reported photochemical radiosynthesis strategies.…”
Section: Introductionmentioning
confidence: 99%